Regulatory and legal basis and European integration aspects of modernization of the system of strategic planning of regional development in the conditions of post-war reconstruction - Karamyshev , Dmytro; Suvorov, Valentyn; Didok, Yuliia (Theory and Practice of Public Administration, 2026)
The article analyzes the regulatory framework and organizational approaches to improving the national system of strategic planning for regional development during post-war reconstruction. Practical recommendations are formulated for optimizing legislation and management tools for strategic planning for regional development, which will allow adapting regional policy to the modern requirements of European integration.The analysis of the regulatory framework indicates a systemic transformation of Ukrainian legislation and its adaptation to the principles of EU regional policy. Thanks to the modernization of the strategic planning system, in particular the introduction of smart specialization, geographic information systems and monitoring by key indicators, Ukraine has created a modern institutional foundation for effective strategic management of regional development.It is substantiated that the adaptation of the regulatory framework in the context of European integration and post-war reconstruction requires solving the following strategic tasks: eliminating inconsistencies and contradictions, duplication of functions and discrepancies between strategic documents of the state, sectoral, regional and local levels; optimization of financial instruments, ensuring a clear link between strategic goals and budget allocations, in particular through transparent mechanisms and attracting funds from European structural funds; increasing the capacity of local governments and Regional Development Agencies, as well as actively involving the public sector in the processes of developing, monitoring and evaluating programs and projects.It has been proven that further improvement of the regulatory framework should be based on the principles of subsidiarity, flexibility and multi-level governance. It is this approach that is critically important for: ensuring sustainable post-war recovery; convergence of regional policy implementation methods; successful integration of the domestic strategic planning system into the EU security and economic space.